Ecological conversion and pluriform Church in the light of the Amazon Sinod - Carbajo Núñez , Martín (Revista Eclesiástica Brasileira, 2022)
Taking into account the documents of the Synod of Bishops for the Pan-Amazon region and the post-synodal exhortation “Querida Amazonia,” this article studies the issue of ecological conversion and the model of a pluriform and well-enculturated Church. In different ways, we are all responsible for the current socio-environmental crisis and, therefore, we all need conversion. The synod proposes Francis of Assisi as an example of the integral conversion we all need. The second part of the article analyzes the new paths that the Synod indicates for the Church in that region so that she may have an Amazonian and indigenous face.